HOTS-Based Interactive E-Books and Student Learning Outcomes: A Systematic Literature Review - Andayani, Andayani; Prabowo, Suryo (PT. Intelektiva Global Nusantara, 2025)
The low mathematical literacy of Indonesian students in global assessments (PISA/TIMSS) drives the search for pedagogical innovation. This systematic literature review analyzes the impact of HOTS (Higher Order Thinking Skills)-based interactive e-books on learning outcomes. A search of the Google Scholar and Scopus databases for the 2017–2025 period, using empirical study inclusion criteria, yielded 31 selected articles. The synthesis results show a consistent positive trend: the implementation of HOTS-based interactive e-books contributes to improved learning outcomes, particularly in mathematics and science, while also developing problem-solving abilities, critical thinking, and student engagement. The findings also identify key supporting factors, such as teacher training, technological readiness, and curriculum relevance. The study concludes that HOTS-based interactive e-books have the potential to be effective learning tools, but their success depends on context and systemic support. The implication is that the integration of technology in education must be supported by teacher capacity building and supportive policies.